The Bondage Breaker. Neil Anderson e Dave Park. Harvest House, (Oregon-EUA): 228p, 1993 (Youth Edition) - Blume, Odair (Vox Scripturae - Revista Teológica Internacional, 1998)
The Bondage Breaker. Neil Anderson e Dave Park. Harvest House, (Oregon-EUA): 228p, 1993 (Youth Edition)